Forensic chemistry as a contextualizing theme in the teaching of chemistry (Research, Society and Development, 2020)
This article is an excerpt from a master's research and aims to present the results of the application of a series of activities related to forensic chemistry for the potentially significant learning of chemistry content, because, due to its presence in the media in several series and television news, it is believed that it has a language that dialogues and arouses the interest of students in scientific knowledge. This research started from the question: Does forensic chemistry as a contextualizing theme lead to meaningful learning? The research approach was a qualitative research-action type. Twenty-four high school students in Chemistry from a private school in the state of São Paulo participated in this research. The activities involved the resolution of a “crime”. For their resolution, the students carried out a series of forensic chemistry experiments: DNA extraction, fingerprint development with coal and iodine, breathalyzer test, footprint development and airbag simulation, in addition to watching thematic videos and answering three evaluative activities (Pre-test; Post-test 1; Post-test 2). The results showed that students more easily understood the chemistry content covered in the activities, there was greater involvement, interest and motivation of students in learning chemistry. Thus, it can be concluded that contextualization from forensic chemistry leads to potentially significant learning of chemistry knowledge.